"\\frac{dx}{x(z+2)}=\\frac{dy}{xz+2yz+2y}=\\frac{dz}{z(z+1)}"
"\\frac{dx}{x(z+2)}=\\frac{dz}{z(z+1)}"
"\\frac{dx}{x}=\\frac{(z+2)dz}{z(z+1)}"
"\\intop\\frac{dx}{x}=\\intop\\frac{(z+2)dz}{z(z+1)}"
"\\intop\\frac{(z+2)dz}{z(z+1)}=\\intop\\frac{dz}{z+1}+2\\intop\\frac{dz}{z(z+1)}"
"\\frac{1}{z(z+1)}=\\frac{A}{z}+\\frac{B}{z+1}"
"A(z+1)+Bz=1"
"A+B=0, A=1, B=-1"
"\\frac{1}{z(z+1)}=\\frac{1}{z}-\\frac{1}{z+1}"
"lnx=ln(z+1)+2lnz-2ln(z+1)+lnc_1"
"lnx=ln(\\frac{c_1z^2}{z+1})"
"\\frac{x(z+1)}{z^2}=c_1"
"\\frac{dy}{xz+2yz+2y}=\\frac{dz}{z(z+1)}"
"\\frac{(z+1)dy}{c_1z^3+2y(z+1)^2}=\\frac{dz}{z(z+1)}"
"\\frac{dy}{dz}-\\frac{y}{z}=\\frac{c_1z^2}{(z+1)^2}"
"y=uv, y'=u'v+uv'"
"u'v+u(v'-\\frac{v}{z})=\\frac{c_1z^2}{(z+1)^2}"
"v'-\\frac{v}{z}=0\\implies v=z"
"u'v=u'z=\\frac{c_1z^2}{(z+1)^2}"
"\\frac{du}{dz}=\\frac{c_1z}{(z+1)^2}"
"u=c_1\\intop\\frac{zdz}{(z+1)^2}"
"\\frac{z}{(z+1)^2}=\\frac{A}{z+1}+\\frac{B}{(z+1)^2}"
"A(z+1)+B=z"
"A=1, A+B=0, B=-1"
"\\frac{z}{(z+1)^2}=\\frac{1}{z+1}-\\frac{1}{(z+1)^2}"
"u=c_1\\intop(\\frac{1}{z+1}-\\frac{1}{(z+1)^2})dz=c_1(ln(z+1)+\\frac{1}{z+1})+c_2"
"y=uv=c_1z(ln(z+1)+\\frac{1}{z+1})+c_2z"
"y=\\frac{x(z+1)}{z}(ln(z+1)+\\frac{1}{z+1})+c_2z"
"\\frac{y}{z}-\\frac{x(z+1)}{z^2}(ln(z+1)+\\frac{1}{z+1})=c_2"
For the curve "(s^2, 0, 2s)" :
"c_1=\\frac{s^2(2s+1)}{4s^2}=\\frac{2s+1}{4}"
"c_2=-\\frac{2s+1}{4}(ln(2s+1)+\\frac{1}{2s+1})"
"c_2=-c_1(ln(4c_1)+\\frac{1}{4c_1})=-c_1ln(4c_1)-\\frac{1}{4}"
Substituting "c_1" and "c_2" we get the integral surface:
"\\frac{y}{z}-\\frac{x(z+1)}{z^2}(ln(z+1)+\\frac{1}{z+1})=-\\frac{x(z+1)}{z^2}ln(\\frac{4x(z+1)}{z^2})-\\frac{1}{4}"
"\\frac{y}{z}-\\frac{x}{z^2}=-\\frac{x(z+1)}{z^2}ln(\\frac{4x}{z^2})-\\frac{1}{4}"
Comments
Leave a comment